Ultrathin polymer membranes with locked intrinsic microporosity for hydrocarbon fractionation - Adam Oxley; Chunchun Ye; Seok Ju Han; Guoke Zhao; Yihao Guo; Xin Shi; Jie Liu; Keenan Smith; Mona Sarter; Lakshmeesha Upadhyaya; Shanshan Hong; Vasilios G. Samaras; et al. (Science, 2026)
Membrane technologies offer an energy-efficient alternative to conventional distillation for hydrocarbon fractionation, but they suffer from a trade-off between fast liquid transport and high molecular selectivity. We report a scalable approach to fabricate polymer membranes with stable interconnected pathways by locking in their intrinsic microporosity. This locking strategy reduces polymer swelling and preserves the subnanometer pore structure in hydrocarbon liquids, resulting in 10-fold higher permeance for synthetic crude oil compared with current state-of-the-art membranes. When applied to Arabian Extra Light crude oil, these membranes achieved excellent size- and class-based separation, removing 99.8% of hydrocarbons containing >15 carbon atoms and 93% of sulfur-containing components. These scalable membranes underpin processes providing rapid and selective hydrocarbon separation, enabling a more sustainable pathway toward crude oil refining.